2005
DOI: 10.2135/cropsci2004.0579
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Histology of Cold‐Hardened Oat Crowns during Recovery from Freezing

Abstract: ABSTRACTa period of low, above-freezing temperatures, termed cold-hardening. Cold-hardening is a critical event in theThe survival of cereal crops during winter depends primarily on the over-wintering physiology of plants (Levitt, 1980 with an increase in freezing tolerance (Steponkus, 1978).stages of recovery after they had been grown and frozen under controlled conditions. Our results confirmed those reported for barleyHowever, it has been difficult to establish cause and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 25 publications
8
54
1
Order By: Relevance
“…2, arrows); this response was more common in oat and least common in rye. This plugging was previously observed in oat and was attributed to bacterial necrosis or possibly coagulated protein in damaged xylem vessels [16]. Somewhat narrow regions of red-staining tissue of varying lengths were also commonly seen throughout the upper part of the crown in frozen samples (Fig.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…2, arrows); this response was more common in oat and least common in rye. This plugging was previously observed in oat and was attributed to bacterial necrosis or possibly coagulated protein in damaged xylem vessels [16]. Somewhat narrow regions of red-staining tissue of varying lengths were also commonly seen throughout the upper part of the crown in frozen samples (Fig.…”
Section: Resultssupporting
confidence: 63%
“…1) in their cold acclimated and unfrozen condition had a similar internal structure to oats as described previously [16]. All four species had multiple stems or tillers, each with its own shoot apex and vascular bundles scattered throughout the crown in a seemingly random fashion.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Previous studies have shown that the apical meristem in the crown is the most freezing tolerant part of the plant [28]. Controlled crown freezing tests on successive generations have also been successfully used as a selection method in a progeny generated from a cross of oat cultivars Wintok and Norline, from which the cold hardy Win/Nor-1 and Win/Nor-10 oat lines were obtained [31].…”
Section: Introductionmentioning
confidence: 99%